2005
DOI: 10.1017/s0022029904000639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormones and growth factors on TGF-β1 expression in bovine mammary epithelial cells

Abstract: The decline of mammary epithelial cell (MEC) number during mammary gland involution in the cow is due to inhibition of proliferation and induction of apoptosis. Transforming growth factorbeta 1 (TGF-b1) belongs to a group of intramammary auto/paracrine inhibitors of bovine MEC growth and inducers of apoptosis. However, the mechanism responsible for the regulation of TGF-b1 expression in MEC is not known. The present study examined the effect of the hormones, growth hormone (GH), somatostatin (STS), 17-b oestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 22 publications
(40 reference statements)
1
45
2
Order By: Relevance
“…In addition to GH1, other important molecules participating to the different GH signal transduction pathways [28] belonged to GN such as GRB2, PLCH2, PLCL2, PLCB4, PLCG1 and SRC or PIK3C2G and PLCZ1, these two latter displaying footprints of selection. GN also contained TGFB1 which is an intramammary auto/paracrine inhibitor of mammary epithelial cells growth and an inducer of apoptosis, which plays a critical role during mammary gland involution [29]. Note that in bovine mammary epithelial cells, GH is also able through its interaction with GHR to suppress expression of TGFB1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to GH1, other important molecules participating to the different GH signal transduction pathways [28] belonged to GN such as GRB2, PLCH2, PLCL2, PLCB4, PLCG1 and SRC or PIK3C2G and PLCZ1, these two latter displaying footprints of selection. GN also contained TGFB1 which is an intramammary auto/paracrine inhibitor of mammary epithelial cells growth and an inducer of apoptosis, which plays a critical role during mammary gland involution [29]. Note that in bovine mammary epithelial cells, GH is also able through its interaction with GHR to suppress expression of TGFB1.…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been reported that FBS contains TGF-b and cells in culture secrete TGF-b [36,[48][49][50], the levels of latent and activated TGF-b were measured in basal media (BM) and CM. The concentration of TGF-b1 was below detectable levels in non-acidified samples of BM and CM collected from normal and CAF cultures treated with 0 ng/ml TGF-b1.…”
Section: Resultsmentioning
confidence: 99%
“…The original description included the claim that these immortalized cells exhibited many characteristics of mammary epithelia, including a cobblestone appearance when grown on solid supports, cytokeratin production, and synthesis of ␣-lactalbumin and ␣ s1 -casein (41). It has since been reported that BME-UV cells respond to a variety of hormones and pharmacological agents with changes in cell signaling, cellular metabolism, proliferation, and apoptosis (6,12,39,40,42). It has also been shown that BME-UV cells grow on a permeable support system to form a confluent, polarized monolayer that is capable of regulated ion transport (29).…”
Section: Discussionmentioning
confidence: 99%